A Storage System for Image File in Cloud Computing - Hongfa Wang (Dianxin kexue)
As cloud computing enters the mainstream，the numbers of virtual machine in one cloud pool is becoming more and more.So，how to quickly and cheaply migrate virtual machines between different hosts for load balance and power savings is becoming one of the hot and tough problems in this filed for the researchers.A distributed storage system was presented，which was called IFSpool.The system was based on Lustre and was designed to achieve the following three goals：high capacity and high extensibility to support thousands of VM images，high I/O throughput for data access，and booting optimization for boot storm.IFSpool combined a queue mechanism and a cache mechanism in a seamless way，to improve I/O throughput and lighten the boot storm by coordinating data access order.The I/O bandwidth and storage capacity of IFSpool can be easily aggregated and extended by adding storage nodes and servers dynamically.The experimental results show that IFSpool is effective and efficient for VM migration.